Socratic questioning for therapists and counselors : learn how to think and intervene like a cognitive behavior therapist - Waltman, Scott H.; Codd, R. Trent, III; McFarr, Lynn M.; Moore, Bret A. (New York : Routledge, 2021)
This book presents a framework for the use of Socratic strategies in psychotherapy and counseling. The framework has been fine-tuned in multiple large-scale cognitive behavior therapy (CBT) training initiatives and is presented and demonstrated with applied case examples. The text is rich with case examples, tips, tricks, strategies, and methods for dealing with the most entrenched of beliefs. The authors draw from diverse therapies and theoretical orientation to present a framework that is flexible and broadly applicable. The book also contains extensive guidance on troubleshooting the Socratic process. Readers will learn how to apply this framework to specialty populations such as patients with borderline personality disorder who are receiving dialectical behavior therapy. Additional chapters contain explicit guidance on how to layer intervention to bring about change in core belief and schema. This book is a must read for therapists in training, early career professionals, supervisors, trainers, and any clinician looking to refine and enhance their ability to use Socratic strategies to bring about lasting change.
OCLC-licensed vendor bibliographic record.
Keywords: Cognitive therapy; Psychotherapy; Questioning; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Psychotherapy / General